Pengaruh Informasi Laba, Ukuran Perusahaan, Dividen dan Leverage terhadap Abnormal Return - Nasharuddin, Muhammad (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2022)
ABSTRACT The purpose of this study is to examine whether or not there is an effect of information on earnings, firm size, dividends and leverage on abnormal returns. The object of this research is a manufacturing company listed on the Indonesia Stock Exchange (IDX). Profit information is related to the problem of meaning that must be attached by report engineers to symbols or cost elements so that profit is useful and meaningful as information, while company size is an indicator that can provide clues about the characteristics or conditions of the company. The research data were collected by using the documentation technique of the sample company's financial statement items. By using purposive sampling, the final sample is 85 companies. Test the research hypothesis using multiple linear regression analysis. The results of the hypothesis test conclude that earnings information, firm size, and leverage have no significant effect on abnormal returns. Research has implications for academic, practical and policy aspects.